ISLAM DAN MODERASI BERAGAMA - Salma Salsabila Syamsudin; Sidik Saipul Ridwan; Siti Maryam Mutoharoh (Melati Institute, 2023)
Religious moderation is a commendable attitude by taking the middle way in religion, not extreme right (fundamentalism), and not extreme left (liberalism).The values in religious moderation are: Tasamuh (tolerance), i'tidal (fair), tawazun (balanced), tawassuth (middle way), musawah (equality), deliberation (negotiation), islah (peace), qudwah (exemplary), awlawiyah (priority), tathawur wa ibtikar (dynamic, innovative).A moderate attitude in Islam is to prioritize tolerance, openness in accepting differences and diversity. Moderate is between fundamentalist and liberal. Islamic moderation is very important to learn, study and apply in daily life in various fields; namely in the social, cultural and religious fields.Ummatan Wasatha is often referred to as religious moderation, because justice is a characteristic of moderate people, in Islam called Wasathiyyah. In the interpretation of Al-Mishbah, Quraisy Shihab interprets the verse that the middle position makes humans not lean or take sides to the left or right, which makes humans fair. It can be seen from any position if humans are in the middle. Whereas in QS. Al-Baqarah verse 238, this verse has the word wustha which refers to prayer. Wustha prayer is prayer in the middle. In the interpretation of Al-Mishbah, the meaning of the sentence ash-shalat al-wustha is the middle prayer. Many scholars understand the Wustha prayer is the Asr prayer, because Asr is the middle prayer between day and night.